Angiotensin II restricted analogs with biological activity in the erythrocytic cycle of Plasmodium falciparum. (25th November 2014) - Torres, Marcelo Der Torossian; Silva, Adriana Farias; de Souza Silva, Leandro; de Sá Pinheiro, Ana Acácia; Oliveira, Vani Xavier Jr.
<x xml:space="preserve">Abstract</x> The anti‐plasmodial activity of conformationally restricted analogs of angiotensin II against Plasmodium gallinaceum has been described. To observe activity against another Plasmodium species, invasion of red blood cells by Plasmodium falciparum was analyzed. Analogs restricted with lactam or disulfide bridges were synthesized to determine their effects and constraints in the peptide–parasite interaction. The analogs were synthesized using tert‐butoxycarbonyl and fluoromethoxycarbonyl solid phase methods, purified by liquid chromatography, and characterized by mass spectrometry. Results indicated that the lactam bridge restricted analogs 1 (Glu‐Asp‐Arg‐Orn‐Val‐Tyr‐Ile‐His‐Pro‐Phe) and 3 (Asp‐Glu‐Arg‐Val‐Orn‐Tyr‐Ile‐His‐Pro‐Phe) showed activity toward inhibition of ring formation stage of P. falciparum erythrocytic cycle, preventing invasion in about 40% of the erythrocytes. The disulfide‐bridged analog 10 (Cys‐Asp‐Arg‐Cys‐Val‐Tyr‐Ile‐His‐Pro‐Phe) was less effective yet significant, showing a 25% decrease in infection of new erythrocytes. In all cases, the peptides presented no pressor activity, and hydrophobic interactions between the aromatic and alkyl amino acid side chains were preserved, a factor proven important in efficacy against P. gallinaceum. In contrast, hydrophilic interactions between the Asp1 carboxyl and Arg2 guanidyl groups proved not to be as important as they were in the case of P. gallinaceum, while interactions between the Arg2 guanidyl and Tyr4 hydroxyl groups were not important in either case. The β‐turn conformation was predominant in all of the active peptides, proving importance in anti‐plasmodial activity. This approach provides insight for understanding the importance of each amino acid residue on the native angiotensin II structure and a new direction for the design of potential chemotherapeutic agents. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.